How the Values and Authentic Leadership Patterns of Kiai in Islamic Boarding School? - Mahani, Muhniansyah Arasyid; Wahyudin, Wahyudin; MOF, Yahya; Suriagiri, Suriagiri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The aim of this study is to explore the values and patterns of authentic leadership exhibited from kiai (Islamic religious leaders) with the context of Islamic Biarding School (Pondok Pesantren). The research how these values and leadership patterns are internalized and manifested the daily of the Islamic Boarding Scchool. This research method qualitative in case study design. Data collected interview participants, observation and document analysis. The data analyzed descriptive techniques, reduction data, display data and verification. The study conducted at Darul Hijrah Islamic Boarding School for Girl in Martapura, South Kalimantan. The findings that the kiai authenthic leadership is characterized core values religiosity (devotion to worship), simplicity, sincerity and sacrifice. These values are internalized both formal and informal social interaction with the pesantren. The concusion figure of the kiai serves a symbol and embodiment of deeply held values that shape the character and ethos of the institution. The implication authenthic leadership values contribute significan to institutional loyalty and the preservation of organizational across other Islamic Boarding Schools.